Honduras : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report assesses the Observance of Standards and Codes on Fiscal Transparency Module for Honduras. Honduras has made good progress in recent years in improving fiscal transparency and the quality and internal consistency of fiscal data. The budget documentation has recently been improved and gives more complete information on the government's fiscal activity in the framework of appropriate institutional, economic, and programmatic classifications. Recent quarterly and monthly reports make it possible to monitor financial execution of the budget and physical execution of investment projects.